The impact of frailty on trauma outcomes using the Clinical Frailty Scale - Thompson, Amari (Eur J Trauma Emerg Surg, 2021)
BACKGROUND: Population ageing is a worldwide phenomenon; thanks to improvements in medical care and living standards. The Office of National Statistics in the UK predicts that the fastest growing age group in coming decades will be those over 85 years. This is reflected in Trauma Audit and Research Network data, which has highlighted a shift in caseload from a majority of young males to elderly patients at UK Major Trauma Centres (MTC). This study of elderly trauma patients admitted to a UK MTC reviews the links between frailty, using the Canadian Study of Health and Aging Clinical Frailty Scale (CFS), and outcomes from trauma. METHODS: A retrospective database review of patients > 65 years old admitted to our MTC was performed. We identified 1125 eligible patients of which 729 had a recorded CFS. Those without a CFS were omitted. The primary outcome measured was in-hospital mortality. Secondary measures were Injury Severity Score, length of stay, trauma team activation on arrival and discharge destination. Multivariate regression analyses were performed using STATA v 15. RESULTS: Those of CFS 5–9 (frail) were 2.6 times more likely to die than the CFS 1–4 (pre-frail) (OR 2.65, 95% CI 1.47–4.78). The frail group was also 56% less likely to have a trauma call on admission (OR 0.44, 95% CI 0.30–0.65) and 61% less likely to be discharged to their usual place of residence (OR 0.39, 95% CI 0.28–0.55). CONCLUSION: We advocate the use of the Clinical Frailty Scale as a screening tool for frailty in trauma patients, highlighting those at risk of increased length of stay and mortality, subsequently assisting healthcare providers with setting realistic expectations with family members. LEVEL OF EVIDENCE: Level III, prognostic and epidemiological